1939
DOI: 10.1063/1.1750419
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Near Ultraviolet Electronic Transition of Benzene

Abstract: The absorption spectrum of benzene at 2800–2200A has been analyzed. The vibrational structure of the system has been found to be in agreement with the selection rules for a forbidden transition (1A1g→1B2u). The transition becomes possible when vibrations of type Eg+ distort the molecule. Only carbon frequencies have been found to be effective. The interpreted data are collected in series on page 211. The analysis is corroborated by comparison with the absorption of solid benzene at —259°C, with the absorption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

1941
1941
2003
2003

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(41 citation statements)
references
References 15 publications
3
38
0
Order By: Relevance
“…The absorption spectrum is plotted in figure 5 (a). Our measurement is well described by previously published data in [20], [21] and [22] apart from in the small wavelength range between 163 to 175 nm. We will use our measurement throughout this paper.…”
Section: Hydrocarbons As Uv Photon Absorberssupporting
confidence: 78%
See 2 more Smart Citations
“…The absorption spectrum is plotted in figure 5 (a). Our measurement is well described by previously published data in [20], [21] and [22] apart from in the small wavelength range between 163 to 175 nm. We will use our measurement throughout this paper.…”
Section: Hydrocarbons As Uv Photon Absorberssupporting
confidence: 78%
“…Figure 5: (a) is the photon absorption coefficient for C 6 H 6 . + is our measurement and the solid line is data replotted from reference [20], [21] and [22]. (b) is the photon absorption coefficient for C 2 H 2 .…”
Section: Hydrocarbons As Uv Photon Absorbersmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of the ultraviolet absorption spectrum of benzene [10] has shown th e vibrational s tructure to b e in agreement with the selection rules for the forbidden electronic transition AI g~ B 2u • It is held tha t this transition is r ender ed possible through the distortion of the benzen e molecule by E; vibrations. Each of th e eigh t absorption bands (see fig.…”
Section: Resultsmentioning
confidence: 59%
“…Since totally symmetric vibratioils lead to the simultaneous rupture of more than one bond if excited sufficiently, it is concluded that ilormal dissociation into two fragments is brought about by non-totally symmetric vibrations, the ground state energy of which is preserved during the electronic transition (25). If a forbidden transition to the fluorescent state is observed owing to the excitation of a non-totally symmetric vibration a s in benzene (26) and naphthalene (24), this vibration is rarely excited sufficiently to cause direct dissociation. Thus the normal photodissociation of polyatomic molecules involves an internal transfer of energy from totally symmetric t o non-totally symmetric vibrations.…”
Section: Introductionmentioning
confidence: 99%